21st Century Challenges of Social Accountability in Post-Soviet Estonian Local Governments - Raudava, Vaike (Advances in Social Sciences Research Journal, 2024)
Contemporary European social work is based on the principles of collective responsibility, human rights, and social justice. The preparation and adoption of the Social Care (Welfare) Act in 1995 followed the general principles of the corresponding law from 1925, in that the responsibility for organizing social welfare fell to local government. Thus, at the end of the 20th century, the main public social work` organizer in Estonia is the local government. Following an accountability-based approach, this research has aimed to explore the accountability of social work in the rural local government. The utilized methodology has been the collective case study (Mills 2010). I followed the information-oriented selection: the cases of maximum variation by size and location. Triangulation has been used as a procedure for acquiring data (Ragin 2011). The lack of state regulation together with an insufficient understanding of social work has affected the local government’s ability to interpret the required duties. An agreement has been missing for sharing the responsibility between the state, the local government and the families. There is also the problem of the local-centered practice, whereby the local government’s own practice of social work has been politically loaded.